Mapping of scientific coverage on education for Entrepreneurship in Higher Education. Issue 1 (31st May 2019) - Durán-Sánchez, Amador; Del Río-Rama, María de la Cruz; Álvarez-García, José; García-Vélez, Diego Fernando
Abstract : Purpose: The purpose of this paper is to present an in-depth analysis of the current state of research related to Education for Entrepreneurship in Higher Education. Education for entrepreneurship is one of the fastest growing fields within academic training worldwide, which is a good indicator of the importance that entrepreneurship and the creation of companies have for the economic development of any society. Education for entrepreneurship is essential, not only to promote an entrepreneurial spirit among young people but also to provide the basic skills, knowledge and innovative attitudes to carry out new business models successfully. Design/methodology/approach: A descriptive bibliometric study was carried out with analysis of citations of 164 articles included in the multidisciplinary database Scopus (Elsevier) until 2017. Findings: The results obtained show a growing interest of the scientific community in its study, as shown by the significant increase both in the number of articles and their citations in recent years. Research limitations/implications: In any bibliometric study, the limitation involved when analysing the results, the choice of a specific database and a specific search equation must be taken into account. With respect to the search terms, those used in this research may not be possible, the inclusion of new terms will alter the results. On the other hand, the aim was not to evaluate the quality of the content of the selected articles at any time, an objective that can be considered in a subsequent investigation, but a descriptive-quantitative analysis of the works and citations related to Education for Entrepreneurship in Higher Education, present in Scopus. To expand the present study, it would be interesting to examine the documents indexed in other databases (Redalyc, Scielo, ProQuest, Directory of Open Access Journals[DOAJ]), together with the possibility of including comparative and overlapping studies between them. Originality/value: The purpose of this work is to serve as a reference for researchers who are developing their studies in the general field of education for entrepreneurship and more specifically in the field of higher education, to improve their knowledge on the most relevant articles, the most productive authors or the key scientific journals that address this topic.